Local and International Experience of ADA University Library in Resource Sharing - Mammadova, Vafa; Allahverdiyeva, Leyla (ADA University Library, 2024)
Resource sharing between libraries has evolved significantly with advancements in technology and changing user needs, enabling more efficient and expansive collaborations.
Keywords: ADA University Library; Library resource sharing — Azerbaijan; International collaboration in libraries